INFORMATION SUPPORT SERVICES OF THE RURAL DEVELOPMENT LIBRARIES IN BANGLADESH - Islam, Md. Shiful; Uddin, Md. Hanif (Malaysian Journal of Library and Information Science, 2005)
Explores the major information systems and services of rural development libraries in Dhaka, Comilla and Bogra districts in Bangladesh. Discusses the situation of these rural development libraries due to the revolution and the advancement made in the information communication technology. Identifies the tools and techniques used in different functional unit of these libraries in order to meet the growing information needs of the rural Bangladeshis. Presents the various problems encountered by these libraries during the period of providing their services and recommends ways for their further development.